Effects of spent engine oil contamination on soybean (Glycine max L. Merril) in an Ultisol - H.E. Ahamefule; J.O. Olaniyan; S.M. Amana; E.K. Eifediyi; E Ihem; C.C. Nwokocha (Journal of Applied Sciences and Environmental Management, 2017)
An experiment was conducted in the University of Nigeria Nsukka Teaching and Research Farm to determine the effect of spent auto-engine oil on soil and soybean in a Randomized Complete Block Design. Treatments were four levels (0, 1, 2 and 3 %) of spent auto-engine oil (SPO). Top soil samples were collected at 0, 12, 24 and 36 months and analyzed. Results indicated that infiltration rates in plots under 3 % SPO was reduced from 1.40 cm h-1 in control plots to the lowest value of 0.07 cm h-1 compared to 0.27 cm h-1 in 1 % treatment in the first 12 months. Plots contaminated with 3 % SPO gave the lowest Ks values of 6.29, 7.68 and 9.43 cm h-1 in the 12th, 24th and 36th months respectively. Data on plant samples showed that 2 % and 3 % SPO contaminations reduced soybean germination from 99 % (control) to 86 and 68 % respectively in the first cropping season whereas 1 % SPO was observed to significantly increase leaf area, dry matter content and grain yield from control values of 52.6 cm2, 3.01 t ha-1 and 0.72 t ha-1 to 54.5 cm2, 4.20 t ha-1 and 0.97 t ha-1 respectively.